2017
DOI: 10.1007/s00726-017-2430-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neurotensin receptor 1 as a potential imaging target in pancreatic ductal adenocarcinoma

Abstract: Pancreatic cancer is one of the deadliest human malignancies and lack of effective diagnostic and therapeutic methods. Accumulating evidence suggests that the neurotensin (NT) and neurotensin receptors (NTRs) play key roles in pancreatic adenocarcinoma growth and survival. In this study, we not only evaluate the NTR1 expression in pancreatic cancer patient samples, but also explore the PET and fluorescence imaging of NTR1 expression in pancreatic cancer animal models. The NTR1 expression was evaluated by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Commonly used tumor markers, such as CA19-9 and CEA, are ineffective for the early detection of PDAC (22). Furthermore, they fail to provide information on the exact location of the cancer lesions, thus making it difficult to determine a therapeutic strategy (23,24). Therefore, identifying prognostic factors for patients with PDAC remains critical, with the aim to develop novel therapeutic approaches and select adequate treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used tumor markers, such as CA19-9 and CEA, are ineffective for the early detection of PDAC (22). Furthermore, they fail to provide information on the exact location of the cancer lesions, thus making it difficult to determine a therapeutic strategy (23,24). Therefore, identifying prognostic factors for patients with PDAC remains critical, with the aim to develop novel therapeutic approaches and select adequate treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Work on NTS 1 receptor as an imaging target by Yin et al (2017) used neurotensin analogues conjugated with Cu‐64 or IRDye800 to label pancreatic adenocarcinoma cell lines. Cu‐64 NT was able to detect AsPC‐1 orthotopic xenografts in mice by PET and of IRDye800‐labelled neurotensin for in vivo fluorescent imaging.…”
Section: Part 2: Functional Data On Gpcrs In Pancreatic Adenocarcinomamentioning
confidence: 99%
“…Larimer et al also reported an 111 In-DOTA labeled ERBB2-targeted SPECT imaging peptide 1-D03 (MEGPSKCCYSLALSH) may serve as a viable candidate for clinical imaging studies of breast carcinoma because of rapid clearance and tumor specificity (Larimer et al 2014 ). Furthermore, gastrin-releasing peptide (Ghosh et al 2019 ), cholecystokinin-2 (Kossatz et al 2013 ), melanocortin-1 (Li et al 2019a ), epidermal growth factor (Ulaner et al 2018 ), neurotensin (Yin et al 2017 ), somatostatin (Liu et al 2018 ) and glucagon-like peptide-1 (Stahle et al 2018 ) receptors have been successfully applied for early cancer imaging diagnosis.…”
Section: Potential Applications Of Targeting Peptidesmentioning
confidence: 99%